The Impact Of Audit Fee, Size Of Public Accounting Firm, Company Size, And Leverage On The Communication Of Key Audit Matters (Implementation Of The First Year Of KAMs Adoption In Independent Auditors' Reports In Indonesia) - Widya Sania; Syahril Ali (Green Publisher Indonesia, 2024)
Auditing standard 701